Pharmaceutical administration for severe hypertension during pregnancy: Network meta-analysis - Deng, Nian-Jia; Xian-Yu, Chen-Yang; Han, Rui-Zheng; Huang, Cheng-Yang; Ma, Yu-Tong; Li, Hui-Jun; Gao, Teng-Yu; Liu, Xin; Zhang, Chao (Frontiers in Pharmacology, 2023)
Aims: To evaluate the efficacy of different pharmacologic treatment for severe hypertension during pregnancy. Methods: Two reviewers searched Ovid MEDLINE, Ovid EMbase, and the Cochrane Library for randomized clinical trials (RCTs) from the establishment of the database to July 15, 2021 that were eligible for inclusion and analyzed the pharmaceuticals used for severe hypertension in pregnancy. Results: 29 relevant trials with 2521 participants were involved. Compared with diazoxide in rate of achieving target blood pressure, other pharmaceuticals, including epoprostenol (RR:1.58, 95%CI:1.01–2.47), hydralazine\dihydralazine (RR:1.57, 95%CI:1.07–2.31), ketanserin (RR:1.67, 95%CI:1.09–2.55), labetalol (RR:1.54, 95%CI:1.04–2.28), nifedipine (RR:1.54, 95%CI:1.04–2.29), and urapidil (RR:1.57, 95%CI:1.00–2.47), were statistically significant in the rate of achieving target blood pressure. According to the SUCRA, diazoxide showed the best therapeutic effect, followed by nicardipine, nifedipine, labetalol, and nitroglycerine. The three pharmaceuticals with the worst therapeutic effect were ketanserin, hydralazine, and urapidil. It is worth noting that the high ranking of the top two pharmaceuticals, including diazoxide and nicardipine, comes from extremely low sample sizes. Other outcomes were reported in the main text. Conclusions: This comprehensive network meta-analysis demonstrated that the nifedipine should be recommended as a strategy for blood pressure management in pregnant women with severe hypertension. Moreover, the conventional pharmaceuticals, including labetalol and hydralazine, showed limited efficacy. However, it was important to note that the instability of hydralazine reducing blood pressure and the high benefit of labetalol with high dosages intakes should also be of concern to clinicians.